1997
DOI: 10.1590/s0100-40421997000300008
|View full text |Cite
|
Sign up to set email alerts
|

O comportamento Fotoquímico dos Complexos Pentaaminas de Rutênio(II) com Ligantes π Insaturados

Abstract: 2+complexes (where L is a π ligand) is presented. The proposed mechanisms and techniques employed for the study of these reactions are discussed. Emphasis is made on the mechanisms that allow the identification of the reactive excited state of the [Ru(NH 3 ) 5 py] 2+ complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…This observation allows to indicate that the photochemical process is dependent on the wavelength and, in general, when it occurs and for the nitrogenated pyridine ligands. For the compounds in the present study, this dependence was not observed for the trans ‐[Ru(NH 3 ) 4 (bpa)(4‐acpy)] +2 complex, which showed no photochemical reaction in any of the filters used.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This observation allows to indicate that the photochemical process is dependent on the wavelength and, in general, when it occurs and for the nitrogenated pyridine ligands. For the compounds in the present study, this dependence was not observed for the trans ‐[Ru(NH 3 ) 4 (bpa)(4‐acpy)] +2 complex, which showed no photochemical reaction in any of the filters used.…”
Section: Resultsmentioning
confidence: 89%
“…On this basis, we conclude that for the series of trans ‐tetraamines studied here, the observed low quantum yield is mainly due to the effective back‐donation process that this series of compounds exhibits. The "excited state tuning" model provides a parameter for classifying compounds according to the processes observed during photolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Dye photosensitized reactions were found to occur for [Ru II L(NH 3 ) 5 ] 2+ (L = pyridine derivatives) [188] and for trans-[Ru II Cl(py)(cyclam)] + [189] in aqueous solutions. For the latter complex, irradiation in the absorption band of rhodamine B, neutral red, Nile blue or cresyl violet in a complex/dye mixture resulted in photosensitized reactions similar to those obtained by direct photolysis [189] without changes in dye absorption.…”
Section: Electronic Spectroscopy and Photochemistrymentioning
confidence: 99%